2016
DOI: 10.1111/soin.12152
|View full text |Cite
|
Sign up to set email alerts
|

The Boundaries of Latino Sport Leadership: How Skin Tone, Ethnicity, and Nationality Construct Baseball's Color Line

Abstract: Ethnoracial minorities constitute a sizeable percentage of the U.S. labor force, but are underrepresented in top management positions. Research examining the leadership gap focuses primarily on blacks and whites without giving ample attention to Latinos, whose experiences differ greatly based on phenotype, birthplace, and citizenship. This research uses an intersectional approach to examine how these categories overlap to influence Latino leadership in Major League Baseball. Using records data and descriptive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…A smaller number of papers have explored stereotypicality within non-Black groups. Among Latino/as, evidence shows that more-stereotypical U.S. Latino/as earn less (Frank, Akresh, & Lu, 2010), have less prestigious jobs (Espino & Franz, 2002; McGovern, 2017), are less likely to enroll in college (Ryabov & Goza, 2014), have fewer non-Latino/a coworkers (Morales, 2008), are stopped more often by police (White, 2015), and are perceived as less intelligent (Hannon, 2014) and overall less positively by others (Kaufman & Wiese, 2012; Ostfeld, 2017; Uhlmann, Dasgupta, Elgueta, Greenwald, & Swanson, 2002), compared with Latino/as with a less-stereotypical appearance. Among Asian Americans, a more-stereotypical appearance predicts more psychological distress (Lee & Thai, 2015) and lower perceived attractiveness (Wilkins, Chan, & Kaiser, 2011).…”
Section: Racial Phenotypic Stereotypicalitymentioning
confidence: 99%
“…A smaller number of papers have explored stereotypicality within non-Black groups. Among Latino/as, evidence shows that more-stereotypical U.S. Latino/as earn less (Frank, Akresh, & Lu, 2010), have less prestigious jobs (Espino & Franz, 2002; McGovern, 2017), are less likely to enroll in college (Ryabov & Goza, 2014), have fewer non-Latino/a coworkers (Morales, 2008), are stopped more often by police (White, 2015), and are perceived as less intelligent (Hannon, 2014) and overall less positively by others (Kaufman & Wiese, 2012; Ostfeld, 2017; Uhlmann, Dasgupta, Elgueta, Greenwald, & Swanson, 2002), compared with Latino/as with a less-stereotypical appearance. Among Asian Americans, a more-stereotypical appearance predicts more psychological distress (Lee & Thai, 2015) and lower perceived attractiveness (Wilkins, Chan, & Kaiser, 2011).…”
Section: Racial Phenotypic Stereotypicalitymentioning
confidence: 99%
“… If there are more than three groups of interest, one-way ANOVA only informs us that at least one pair of means is different but does not identify this comparison. Chi-square ( Bouris & Hill, 2017 ; Landstedt & Gådin, 2012 ; McGovern, 2017 ) The chi-squared test evaluates whether two categorical variables are related to each other in the same population 163–1663 2 No Chi-square analysis to evaluate an intersectionality hypothesis involves creation of a categorical variable combining 2 (or more) factors and evaluating whether this variable is predictive of a categorical outcome of interest. Chi-square is robust to data distribution and can be useful when parametric assumptions of other tests cannot be fulfilled.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, Morales (2008) finds that skin color can lead to Latinos being segmented within labor markets, with darker skin Latinos being stratified into lower-waged sectors of the labor market. Examining the impact of skin color on occupational prestige, Espino and Franz (2002) found that skin color magnified lower prestige for Latinos of Mexican and Cuban origin, but not for Puerto Ricans (McGovern 2017). Specific to political equality, Tafoya (2004) found that a U.S.-born Latino's “whiteness” was clearly and consistently associated with higher social status, higher levels of civic participation, and a stronger sense of social acceptance.…”
Section: Skin Color/phenotypesmentioning
confidence: 99%